ANALISIS DAMPAK COVID-19 TERHADAP PERUBAHAN HARGA DAN VOLUME TRANSAKSI SAHAM PADA SUB SEKTOR FARMASI YANG TERDAFTAR DIBURSA EFEK INDONESIA - Purnama Panggabean; Septony B. Siahaan; Duma Megaria Elisabeth (Universitas Methodist Indonesia, 2023)
This study aims to determine whether there are significant differences between stock prices and trading volume before and after Covid-19 in pharmaceutical companies listed on the Indonesia Stock Exchange. The sample collection technique used purposive sampling method. Based on the determine criteria, this research obtained 10 companies sample. This study uses secondary data with descriptive analysis methods and quantitative analysis. Data analysis in this study used the Wilcoxon signed rank test, the data for this study were taken 30 days before and 30 days after the announcement of Covid-19 in Indonesia. The results showed that there were significant differences in stock prices and trading volume before and after Covid-19 in Indonesia.